Distinguishing between overdrive excited and suppressed ventricular beats in guinea pig ventricular myocardium - Greer-Short, Amara; Poelzing, Steven (Frontiers in Physiology, 2015)
Rapid ventricular pacing rates induces two types of beats following pacing cessation: recovery cycle length (RCL) prolongation (overdrive suppression) and RCL shortening (overdrive excitation). The goals of this study were to compare common experimental protocols for studying triggered activity in whole-heart preparations and differentiate between recovery beats using a new methodology. Post-pacing recovery beat cycle length (RCL) and QRS were normalized to pre-paced R-R and QRS intervals and analyzed using a K-means clustering algorithm. Control hearts only produced suppressed beats: RCL ratio increased with rapid pacing (25±4.0%, n=10) without changing QRS duration. Rapid pacing during hypercalcemia + hypothermia (5.5 mM and 34°C) produced significantly earlier excited beats (53±14%, n=5) with wider QRS durations (58±6.3%, n=5) than suppressed beats. Digoxin + hypothermia (0.75 M) produced the most excited beats with significantly earlier RCL (44±3.2%, n=6) and wider QRS (60±3.1%, n=6) ratios relative to suppressed beats. Increasing pacing further shortened RCL (30±7.8%, n=6). In a prospective study, TTX (100 nM) increased RCL ratio (15±6.0%, n=10) without changing the QRS duration of excited beats. The algorithm was compared to a cross-correlation analysis with 93% sensitivity and 94% specificity. This ECG based algorithm distinguishes between triggered and automatic activity.